2023
DOI: 10.3390/microorganisms11061543
|View full text |Cite
|
Sign up to set email alerts
|

The Slaughterhouse as Hotspot of CC1 and CC6 Listeria monocytogenes Strains with Hypervirulent Profiles in an Integrated Poultry Chain of Italy

Abstract: In Europe, very few studies are available regarding the diversity of Listeria monocytogenes (L. monocytogenes) clonal complexes (CCs) and sequence types (ST) in poultry and on the related typing of isolates using whole genome sequencing (WGS). In this study, we used a WGS approach to type 122 L. monocytogenes strains isolated from chicken neck skin samples collected in two different slaughterhouses of an integrated Italian poultry company. The studied strains were classified into five CCs: CC1-ST1 (21.3%), CC6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…Moreover, our study revealed the presence of a hypervirulent strain, ST6/VT19, associated with several epidemic outbreaks, particularly in Europe in 2015-2020, showing a wide and intercontinental diffusion [39]. Indeed, due to the worldwide commercialization of food products, hypervirulent strains spread rapidly over large geographic areas, causing multi-country outbreaks.…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, our study revealed the presence of a hypervirulent strain, ST6/VT19, associated with several epidemic outbreaks, particularly in Europe in 2015-2020, showing a wide and intercontinental diffusion [39]. Indeed, due to the worldwide commercialization of food products, hypervirulent strains spread rapidly over large geographic areas, causing multi-country outbreaks.…”
Section: Discussionmentioning
confidence: 76%
“…This poses significant concerns for food business operators (FBOs), as it can lead to outbreaks due to crosscontamination when food products come into contact with inadequately cleaned surfaces. A recent study detected hypervirulent L. monocytogenes strains in slaughterhouses (Guidi et al 2023), which is a particularly important finding as there is an increasing trend in listeriosis cases in Sweden (Figure 3).…”
Section: Listeria Monocytogenesmentioning
confidence: 80%
“…NDM-CRE exhibited a significant increase in detection rate within the livestock production chain, in which the slaughterhouses are the hotspots for cross-contamination of NDM-CRE. Slaughterhouse was proved to play a significant role in the contamination and dissemination of various pathogens including Salmonella [ 33 ], Listeria monocytogenes [ 34 ] and particularly the antimicrobial resistance (AMR) strains [ 35 ]. Here, in this study, although NDM-negative isolates presented in NDM-free chicken and pig farms, the livestock from these NDM-free farms are transported to the slaughterhouses, where the livestock from NDM-positive farms entered and slaughtered as well, cross-contaminated with NDM-CRE in meat processing.…”
Section: Discussionmentioning
confidence: 99%